(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
This text aims to introduce the reader to the process of creating an ecologically sustainable show based on sustainable artistic practices. I seek, in this way, to propose some Contributions to an eco-scenic art, which arise from the experience, reflections and conclusions of the process of creation, staging and adaptation of the large-format puppet work: Water, the treasure of the Wetland. The civilizational crisis that has dragged on for some decades, and that has marked this era of the Anthropocene with a destructive force of the planet and of those who live in it, takes on a global and catastrophic dimension since the advent of the Covid-19 pandemic in 2020 In the midst of these cataclysms, the Uruguayan company of Títeres del Timbó immerses itself in the creation, staging and circulation of an animated show on living matter, built from natural resources and flexible to new challenges. Understanding that art is a deep human need, and that many times in the beauty of its metaphors an expression of the truth and the unknown is found, this text proposes some contributions for the gestation of an eco-scenic art, a new art, not only possible, but necessary.